Physical Plant Design and Engineering Controls to Reduce Hospital-Acquired Infections - JM Conly; BL Johnston (Canadian Journal of Infectious Diseases and Medical Microbiology)
The importance of the environment as a reservoir for microorganisms implicated in disease transmission in the hospital setting has been increasingly recognized, especially with respect to dialysis units, ventilation in specialized areas, and the proper use of disinfectants (1). Inherent within the environmental setting is the importance of physical plant design. Several studies have underscored the importance of optimizing design standards to maximize patient and health care worker (HCW) safety, including the prevention of hospital-acquired infections in patients (2-6). Ulrich et al (7) recently completed an evidence-based review, entitled 'The role of the physical environment in the hospital of the 21st century: A once-in-a-lifetime opportunity', for the Center for Health Design in California (USA), which was funded by the Robert Wood Johnson Foundation. Ulrich and colleagues identified over 600 studies that examined the hospital environment and its effects on staff effectiveness, patient safety, patient and family stress, quality and costs. They suggested that one of the important elements in improving patient safety is the reduction of the risk of hospital-acquired infections through improved facility design.